2021
DOI: 10.1002/mus.27249
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine may be effective for treatment of paramyotonia congenita

Abstract: Introduction/Aims: Paramyotonia congenita (PMC) is a skeletal muscle sodium channelopathy characterized by paradoxical myotonia, cold sensitivity, and exercise/ cold-induced paralysis. Treatment with sodium-channel-blocking antiarrhythmic agents may expose patients to a risk of arrhythmia or may be poorly tolerated or ineffective. In this study we explored the effectiveness of non-antiarrhythmic sodiumchannel blockers in two patients with PMC.Methods: Earlier treatment with mexiletine was discontinued for gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, we propose the use of MVRC as a biomarker for target engagement of drugs developed to influence muscle excitability, such as novel (subtype‐specific) Na V blockers, 19 , 20 or existing sodium‐ or potassium channel modulating therapies proposed as new treatments for myotonia. 21 , 22 , 23 This biomarker may therefore be used for proof of target engagement but may also facilitate an informed choice of the dose level in the translation from phase I studies in healthy subjects to phase II and III studies in patient populations. Furthermore, MVRCs may also be used in the translational phase between preclinical and clinical studies because the measurement can also be performed in animal studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we propose the use of MVRC as a biomarker for target engagement of drugs developed to influence muscle excitability, such as novel (subtype‐specific) Na V blockers, 19 , 20 or existing sodium‐ or potassium channel modulating therapies proposed as new treatments for myotonia. 21 , 22 , 23 This biomarker may therefore be used for proof of target engagement but may also facilitate an informed choice of the dose level in the translation from phase I studies in healthy subjects to phase II and III studies in patient populations. Furthermore, MVRCs may also be used in the translational phase between preclinical and clinical studies because the measurement can also be performed in animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Whether effects of compounds developed for various NMDs can be detected using MVRC will have to be confirmed in future studies. However, we propose the use of MVRC as a biomarker for target engagement of drugs developed to influence muscle excitability, such as novel (subtype‐specific) Na V blockers, 19,20 or existing sodium‐ or potassium channel modulating therapies proposed as new treatments for myotonia 21–23 . This biomarker may therefore be used for proof of target engagement but may also facilitate an informed choice of the dose level in the translation from phase I studies in healthy subjects to phase II and III studies in patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative treatments for myotonia may include ranolazine and lamotrigine which enhance the slow inactivation of sodium channels. 21,22 Ravaglia et al 23 recently reported another possible compound that might be useful in treating stiffness in paramyotonia congenita. They treated 2 patients with buprenorphine, a drug that is typically used for opiate addiction often in combination with naloxone.…”
Section: Treatment Of Nondystrophic Channelopathiesmentioning
confidence: 99%